Effectiveness and safety of electrical moxibustion for knee osteoarthritis: A multicenter, randomized, assessor-blinded, parallel-group clinical trial. (September 2020) - Kang, Ha-Ra; Lee, Yeon-Sun; Kim, Seon-Hye; Sung, Won-Suk; Jung, Chan-Yung; Cho, Hyun-Seok; Lee, Seung-Deok; Kim, Kyung-Ho; Kim, Eun-Jung
Highlights: Electrical moxibustion treatment reduced pain and improved function in patients with knee osteoarthritis. Fewer participants reported adverse events related to treatment in the electrical moxibustion group. Our findings showed the feasibility of electrical moxibustion being used in the treatment for knee osteoarthritis patients. Abstract: Background: The prevalence of knee osteoarthritis (KOA) is increasing, and it has emerged as a major health issue. Studies have been reported that moxibustion is effective for treating KOA, but conventional moxibustion is difficult to control the intensity of stimulation and causes smoke, harmful gases, or odors. An electrical moxibustion (EM) device was developed to solve these problems, so we conducted this study to evaluate the effectiveness and safety of EM as a treatment for KOA. Methods: This is a multicenter, randomized, assessor-blinded, parallel-group clinical trial. Participants with KOA were randomly allocated into EM, traditional indirect moxibustion (TIM), or usual care groups. The moxibustion groups were received 12 sessions of moxibustion treatment at six acupuncture points (ST36, ST35, ST34, SP9, EX-LE4, SP10) over a period of 6 weeks. The usual care group was received usual treatment and self-care. The primary outcome was the degree of pain measured by numerical rating scale (NRS). The second outcomes were measured using visual analog scale, Korean version of the Western Ontario and McMaster Universities osteoarthritis index, patient global assessment, European quality of life five dimension five level scale, and warm sense threshold and heat pain threshold. For safety assessment, laboratory test and adverse events (AEs) were recorded. Results: A total of 138 participants were assigned. While there was no significant NRS change in the usual care, EM and TIM showed significant decrease after treatment. Compared to the usual care, the mean change of NRS in the EM and TIM was significantly different, but there was no significance between two groups. Regarding secondary outcomes, EM and TIM also showed significant difference compared to the usual care, but there was no significance between two groups. Regarding safety assessment, while usual care showed significant safety among three groups, EM showed seven treatment-related AEs by four participants compared TIM's 10 events by 10 participants. In addition, there was no blister caused by burns in the EM, which occurred four cases in the TIM. Conclusion: This study shows that EM is effective to improve the pain and function by KOA with a certain level of safety.